SARS-CoV-2 is transmitted via contact and via the air between ferrets - Richard, Mathilde; Kok, Adinda; de Meulder, Dennis; Bestebroer, Theo M.; Lamers, Mart M.; Okba, Nisreen M. A.; Fentener van Vlissingen, Martje; Rockx, Barry; Haagmans, Bart L.; Koopmans, Marion P. G.; Fouchier, Ron A. M.; Herfst, Sander (Nature communications, 2020)
SARS-CoV-2, a coronavirus that emerged in late 2019, has spread rapidly worldwide, and information about the modes of transmission of SARS-CoV-2 among humans is critical to apply appropriate infection control measures and to slow its spread. Here we show that SARS-CoV-2 is transmitted efficiently via direct contact and via the air (via respiratory droplets and/or aerosols) between ferrets, 1 to 3 days and 3 to 7 days after exposure respectively. The pattern of virus shedding in the direct contact and indirect recipient ferrets is similar to that of the inoculated ferrets and infectious virus is isolated from all positive animals, showing that ferrets are productively infected via either route. This study provides experimental evidence of robust transmission of SARS-CoV-2 via the air, supporting the implementation of community-level social distancing measures currently applied in many countries in the world and informing decisions on infection control measures in healthcare settings. SARS-CoV-2 has rapidly spread globally and animal models to study transmission are needed. Here, Richard et al. show efficient transmission of SARS-CoV-2 between ferrets via direct contact and via the air, through respiratory droplets and/or aerosols.